EDUCATION-JOB MISMATCH IN THE LABOR MARKET OF KAZAKHSTAN: IMPLICATIONS FOR PUBLIC POLICY - Serikbayeva, Balzhan (Nazarbayev University Graduate School of Public Policy, 2022)
Considering the expansion of post-secondary education, its expensiveness and the costs associated with ineffective use of available human capital, the issue of the match between worker education and job is an important research question to study. The current study investigates education-job mismatches among Kazakhstani workers, using the mixed methods research design. Based on the nationally representative Labor Force Survey data for the period 2014-2018, the quantitative part of the research examines the incidence, determinants of education-job mismatches and their effects on individual earnings. For these purposes, we estimate binary logit models and OLS regressions. Ordered probit models are employed to check the robustness of the OLS findings on the earnings effects of mismatches. The qualitative inquiry implemented through online focus groups pursues the goal of complementing the findings of the quantitative study by exploring multiple perspectives of experts on the importance of education-job match, reasons for educational mismatches1, and the role of education-system and labor market-related factors in the matching of education to employment. The empirical analysis shows that human capital and employment characteristics are likely to have much more impact on the probability of being mismatched than individuals’ socio-demographic characteristics. We also find that relative to being well-matched, both vertical and horizontal mismatches have significant negative effects on individual earnings. The earnings penalty is found to be greatest for both vertically and horizontally mismatched (double mismatched) workers. The findings from the focus groups indicate that constrained career choices, labor demand-supply gaps, flaws in the education system, the lack of career guidance, inflated job expectations, unfavourable employment and macroeconomic conditions present additional important factors that could contribute to explaining education-job mismatches. The study has important policy implications.
Keywords: Type of access: Open; education-job mismatch; vertical mismatch; horizontal mismatch; overeducation; earnings; public policy; Kazakhstan